2008
DOI: 10.1007/s10562-008-9720-1
|View full text |Cite
|
Sign up to set email alerts
|

Selective Hydrogenation of Nitrobenzene to Aniline over Ru/SBA-15 Catalysts

Abstract: A series of Ru/SBA-15 catalysts (0.5-6.0 wt%) are prepared by impregnation method. The catalysts were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), temperature programmed reduction (TPR), X-ray photoelectron spectroscopy (XPS), CO-chemisorption, surface area and pore-size distribution measurements. The catalytic activities were evaluated for the vapor phase hydrogenation of nitrobenzene. The dispersion measured by CO-uptake values suggests decrease in dispersion with increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 30 publications
2
53
0
Order By: Relevance
“…It was reported that the deposition of Ni (10 wt%) on SBA-15 support by liquid phase reductive deposition method did not alter the mesoporous structure of SBA-15 [44]. Similar observation was reported for Ru/SBA-15 catalysts [45]. In addition, intactness of SBA-15 structure was also reported for Ni/SBA-15 catalysts [46].…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…It was reported that the deposition of Ni (10 wt%) on SBA-15 support by liquid phase reductive deposition method did not alter the mesoporous structure of SBA-15 [44]. Similar observation was reported for Ru/SBA-15 catalysts [45]. In addition, intactness of SBA-15 structure was also reported for Ni/SBA-15 catalysts [46].…”
Section: Resultssupporting
confidence: 74%
“…Among the SiO 2 -based supports, ordered mesoporous silica materials such as SBA-15 are unique, owing to their remarkable properties such as high surface area (> 700 m 2 /g), thermal stability, and uniform pore size (46-300 Å). This high surface area and uniform pore size of SBA-15 facilitate the high dispersion of active component even at higher loadings by retaining the mesoporous structure of SBA-15 [44][45][46][47]. Mesoporous materials have found potential applications in catalysis, as adsorbents, separation, optoelectronics, sensors, as supports, fabrication of nanostructure materials and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Table 4 highlights the superior performance of the present catalytic system when compared to previously published catalysts for NB hydrogenation in vapour phase conditions. Higher NB conversion (96.5 %) with nearly 100 % selectivity towards aniline at 275°C was reported over Ru/SBA-15 catalyst at atmospheric pressure when compared to the SiO 2 -and Al 2 O 3 -supported Ru catalysts, which clearly shows the advantage of SBA-15 support [38]. Among the Pd-supported MgO-Al 2 O 3 (hydrotalcite) catalysts with different Pd contents, a catalyst with 0.5 wt% Pd exhibited very high NB conversion (97 %) with nearly 100 % selectivity towards AN at atmospheric pressure and at 225°C [39].…”
Section: Effect Of Time On Streammentioning
confidence: 77%
“…17 Aminosilane grafting to MCM-41 and further incorporation of RuNP caused a considerable decrease in the 10 XRD intensity. 25 18 In these materials, both the intensity and resolution of the peaks are not decreased by anchoring RuNP, probably because the size of the RuNP (ca. 3 nm) does not affect the pores of SBA-15 (ca.…”
Section: Catalysts Characterizationmentioning
confidence: 98%
“…20 Otherwise, SBA-15 type materials showed an abrupt step at higher relative pressures (P/Po = 0.6-0.8) as expected for bigger pore size silicas. 18 Finally, HMS 40 solids did not show an abrupt step in their isotherms profiles due to the broad pore size distributions 3 Table 1 summarizes BJH pore size distributions calculated from the adsorption branches of the isotherms and BET surface areas of the new solids. As expected, in all cases both the pore diameter and the surface area 45 decreased after the incorporation of the anchored RuNP into the mesopores.…”
Section: Catalysts Characterizationmentioning
confidence: 99%